1997
DOI: 10.1002/(sici)1099-0984(199706)11:2<101::aid-per279>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

The paranoid person: cognitive motivations and personality traits

Abstract: The purpose was to contribute to a better understanding of the personality structure and dynamics of paranoia. In study 1, 29 paranoid patients and three control groups (30 schizophrenics, 27 depressives, and 64 healthy subjects) were administered the Cognitive Orientation (CO) Questionnaire of Paranoia, which included beliefs of four types (goals, norms, about self, and general) referring to 44 themes (e.g. masculinity, strength). Discriminant analyses (based on longer and shorter versions of the questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The answer that is proposed in the present article is that traits are patterns of meaning assignment tendencies . This answer, which has first been suggested in the book entitled The Cognitive Foundations of Personality Traits (Kreitler & Kreitler, ) and later elaborated upon in many further studies and publications (e.g., Kreitler, , ; Kreitler & Kreitler, ), is based on the assumption that the sphere of meaning is the theoretical abode for traits. In the next sections, the system of meaning will be presented, as well as the empirical basis for the proposed definition of traits and its theoretical and practical implications.…”
Section: The Problem Of Traitsmentioning
confidence: 98%
See 1 more Smart Citation
“…The answer that is proposed in the present article is that traits are patterns of meaning assignment tendencies . This answer, which has first been suggested in the book entitled The Cognitive Foundations of Personality Traits (Kreitler & Kreitler, ) and later elaborated upon in many further studies and publications (e.g., Kreitler, , ; Kreitler & Kreitler, ), is based on the assumption that the sphere of meaning is the theoretical abode for traits. In the next sections, the system of meaning will be presented, as well as the empirical basis for the proposed definition of traits and its theoretical and practical implications.…”
Section: The Problem Of Traitsmentioning
confidence: 98%
“…However, a study with paranoid patients showed that applying the procedure of assessing traits by the Test of Meanings (see above) enabled assessing 124 personality traits in a paranoid and healthy sample on the basis of the same patterns of meaning assignment tendencies (Kreitler & Kreitelr, ). Further studies are needed for specifying in which samples the patterns of meaning assignment tendencies corresponding to traits are affected appreciably by the mental disorders.…”
Section: Personality Traits and Meaningmentioning
confidence: 99%
“…Again, as in the case of cognitive acts, the pattern of meaning variables may be seen as providing a description of the contents and processes involved in the enactment of the specific trait. For example, the meaning variables in the pattern corresponding to extraversion are characterized by high salience of the meaning dimensions of action, sensory qualities, temporal qualities and belongingness of objects, as well as low salience of the meaning dimensions of internal sensations and cognitive qualities [18,43]. If the individual's meaning profile includes a sufficient proportion of the meaning variables found also in the pattern corresponding to the particular personality trait, it is highly likely that the individual scores high on that personality trait.…”
Section: Meaning: the Theory And The Systemmentioning
confidence: 99%
“…The availability of the program is often assumed, and may be tested by means of observation or self-report. As noted, the described method enabled successful predictions of different behaviors (e.g., achievement, reactions to success and failure, coming on time, reactions to danger, smoking, quitting smoking, overeating, undergoing cancer-detection tests, curiosity, planning, assertiveness, paranoia, communicability, applying defenses, deceiving, compliance in diabetics) in different populations (healthy adults, children, retarded or psychopathological individuals) (Kreitler, Chaitchik, Kreitler, & Weissler, 1994;, 1991, 1993, 1997Kreitler, Shahar, & Kreitler, 1976;Kreitler, Schwartz, & Kreitler, 1987;Lobel, 1982;Nurymberg, Kreitler, & Weissler, 1996;Tipton & Riebsame, 1987;Westhoff & Halbach-Suarez, 1989).…”
mentioning
confidence: 94%